Exploring Exchange Bias Coupling in Fe3−δO4@CoO Core–Shell Nanoparticle 2D Assemblies. (25th April 2018) - Dolci, Mathias; Liu, Yu; Liu, Xiaojie; Leuvrey, Cedric; Derory, Alain; Begin, Dominique; Begin‐Colin, Sylvie; Pichon, Benoit P.
Abstract: Core‐shell ferro(i)magnetic@antiferromagnetic (F(i)M@AFM) nanoparticles exhibiting exchange bias coupling are very promising to push back the superparamagnetic limits. However, their intrinsic magnetic properties can be strongly affected by interparticle interactions. This work reports on the collective properties of Fe3– d O4 @CoO core‐shell nanoparticles as function of the structure of their assembly. The structure of nanoparticle assembly is controlled by a copper (I) catalyzed alkyne–azide cycloaddition (CuAAC) "click" reaction between complementary functional groups located at the surface of both substrates and nanoparticles. 2D arrays of nanoparticles with tunable sizes ranging from clusters of few nanoparticles to a dense and homogenous monolayer were prepared. The spatial arrangement of nanoparticles strongly influences the exchange bias coupling which is significantly enhanced for large 2D nanoparticle assemblies and, even more in 3D assemblies such as powder, which favour weak and random dipolar interactions. Abstract : Core–shell Fe3 O4 @CoO nanoparticles are immobilized onto a substrate by taking advantage of copper(I) catalyzed alkyne–azide cycloaddition click reaction in order to produce highly stable assemblies. Exchange bias properties in nanoparticle assemblies are investigated as function of 2D clusters, 2D monolayer, and 3D random aggregates. It is shown that exchange bias coupling in ferro(i)magnetic (FiM)/antiferromagnetic core–shell nanoparticles is significantly dependent on the spatial arrangement of nanoparticles.